Clival chordoma presenting as a parapharyngeal mass: a diagnostic challenge - Pradhan, Prita; Biswal, Rudra Narayan; Rout, Khageswar; Panigrahi, Ranjita; Misra, Pranati; Senapati, Urmila; Rath, Jayasree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Though the parapharyngeal space is sites of primary involvement by neoplastic process, they can rarely house masses descending from a base of skull tumour. Chordoma is an uncommon tumour of the skull base and sacrococcyx. Originating from the notochordal remnants, they are locally aggressive causing lytic destruction of the adjacent bony structures, particularly in the base of the skull. The use of surgery and adjuvant high-dose proton RT is documented to produce best results. Here we report a diagnostic challenge posed by a chordoma occurring as a parapharyngeal mass in a 68 year old male.